A droplet-based millifluidic method for studying ice and gas hydrate nucleation. (31st December 2018) - Atig, Dyhia; Touil, Abdelhafid; Ildefonso, Manuel; Marlin, Laurent; Bouriat, Patrick; Broseta, Daniel
Highlights: A new method is devised for studying crystal nucleation under controlled pressure. The method relies on observing in a capillary a train of water drops in a carrier oil. The effects of hydrate-formers dissolved in water and carrier oil are investigated. The carrier oil itself can also be a hydrate-former, e.g., cyclopentane. Zooming in a single drop allows crystal growth and melting processes to be observed. Abstract: We design and implement a simple and versatile droplet-based millifluidic method for investigating nucleation and growth processes in crystal-forming aqueous systems. It consists in generating and storing in a transparent capillary a train of identical and regularly-spaced droplets of an aqueous phase in a carrier oil phase, and then in video-monitoring crystal nucleation and subsequent growth and melting events as temperature and/or pressure are varied. Compared to previous investigations, the novelty is the possibility of working with aqueous solutions containing dissolved gas under controlled pressure, thus opening the way to gas hydrate studies. In the absence of dissolved gas, i.e., at ambient pressure, we observe ice nucleation to be weakly promoted by titanium oxide and montmorillonite particles, and strongly promoted by silver iodide, in agreement with literature results. Ice nucleation is also promoted when the carrier oil is more wetting towards the capillary, which is the case for fluorinated oil as compared to n -hexane. With cyclopentane, a hydrate-former, as the carrier oil, and dissolved CO2, also a hydrate-former and a "help gas" for cyclopentane hydrate formation, we find evidence for hydrate nucleation along with that of ice, and monitor the different solid phases as temperature varies.